2015
DOI: 10.1166/jnn.2015.9189
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-Loaded Chitosan-Coated Nanoparticles as a New Approach for the Local Treatment of Oral Cavity Cancer

Abstract: Mucoadhesive nanoparticles loaded with curcumin were developed as a new approach to deliver curcumin for the local treatment of oral cancer. PCL nanoparticles coated with chitosan displaying different molar masses were prepared by using the nanoprecipitation technique. The mucoadhesive properties of nanoparticle suspensions were demonstrated by their strong ability to interact with the glycoprotein mucin through electrostatic interactions. Similar permeation profiles of curcumin loaded in uncoated and chitosan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 0 publications
1
65
0
Order By: Relevance
“…Concentration and purity can be examined with the help of dynamic light scattering (DLS), that is based on Brownian NP movement. 46 Typically, NP characterization is also performed through ζ-potential analysis. The ζ-potential is a key indicator of the stability of NP suspensions, and DLS characterizes particle size and size distribution.…”
Section: Nanosystem Imaging Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentration and purity can be examined with the help of dynamic light scattering (DLS), that is based on Brownian NP movement. 46 Typically, NP characterization is also performed through ζ-potential analysis. The ζ-potential is a key indicator of the stability of NP suspensions, and DLS characterizes particle size and size distribution.…”
Section: Nanosystem Imaging Methodsmentioning
confidence: 99%
“…The ζ-potential is a key indicator of the stability of NP suspensions, and DLS characterizes particle size and size distribution. 46 After the particles are characterized, the first layer of biological assessment of their effects takes place in in vitro conditions. In order to follow and quantify the speed of their internalization, two major types of microscopy can be used: fluorescence microscopy and electronic microscopy.…”
Section: Nanosystem Imaging Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Original Articles 16-26. Chitosan nanocarriers could be used in future dental applications 9 such as in dentin pulp regeneration procedures, [10][11] in bone regeneration techniques, 12 in endodontics [13][14][15] or in periodontal therapy. 12,16 Moreover, chitosan containing NPs were able to transport antitumour substances to different cancer cell lines, [17][18][19] including oral cancer cells. [18][19] Despite numerous scientifi c reports regarding organic nanomaterials in medicine, more experiments are needed in order to asses the effects of organic NPs on the oral mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…12,16 Moreover, chitosan containing NPs were able to transport antitumour substances to different cancer cell lines, [17][18][19] including oral cancer cells. [18][19] Despite numerous scientifi c reports regarding organic nanomaterials in medicine, more experiments are needed in order to asses the effects of organic NPs on the oral mucosa. It has been shown that the interactions between NPs and cells depends on the cell type, as well as on the size and surface charge of NPs.…”
Section: Introductionmentioning
confidence: 99%